Philippine Air Transportation: Impact and Challenges - Yu, Krista Danielle (Animo Repository, 2019)
With the Philippines’ archipelagic geography, air transport is the most efficient way to connect its islands and boost economic activities. Using the latest Philippine input-output tables (National Statistical Coordination Board, 2006; Philippine Statistics Authority, 2014, 2017), the air transport sector proves to be the leading driver of economic activities. Ranking first relative to all other sectors in the economy, in terms of backward linkages, indicates its general dependence on the rest of the economy for inputs to the services that it provides.